رسول اللہ ﷺ کے حقوق: منتخب عربی ادب سیرت کاتحقیقی و تجزیاتی مطالعہ: Rights of Prophet Muhammad (S.A.W) Research and Analytical Study of Selected Seerah Literature in Arabic - Muhammad Rafiq; Dr. Muhammad Saad Siddiqui (MEI, 2023)
To believe in Prophecy of Muhammad (S.A.W) and to love him (S.A.W) is the basic and the fundamental right of Muhammad (S.A.W) on a Muslim and the first obligation of Islam. Without it neither the monolatry of Allah Almighty is reliable nor the faith and conduct. There are two levels of love of Muhammad (S.A.W). The least is that a Muslim has some love of Prophet (S.A.W) in his heart because a person who does not have the love of Muhammad (S.A.W) is deprived of faith and the perfect level is to love Muhammad (S.A.W) more than every thing. Because Muhammad’s (S.A.W) personality is like a candle and the source of promotion and awareness through which the whole humanity earned the wealth of faith and believe, knowledge and philosophy and the right religion. So any kind of welfare and prosperity cannot be achieved by turning away from Muhammad (S.A.W). Several rights of Muhammad (S.A.W.) are defined in Quran and Sunnah. Muslims must be aware of them. Due to this significance, from early centuries of Islam many Muslim scholars and meditators wrote books about this topic with different titles and methodologies like Kutub-e-Maghazi, Kutub-e-Seerat, Kutub-e-Dalail, Kutub-e-Aalaam, Kutub-e-Moajizaat and Kutub-e-Shamail etc. In this perspective especially Sharaf-ul- Mustafa of Imam Abu Saad Al- Kharkoshi, Al- Shifa of Qazi Ayyaaz and Al-Saarim Al-Maslool of Imam Ibn-e-Timiyah are worth mentioning. They discussed different rights of Muhammad (S.A.W) with detail and reasons in their books. Among these books “ Al-Shifa Fi Taarif Huqooq Al-Mustafa” of Qazi Ayyaz got much appreciation than any other. Due to the appropriateness with theme, knowledge and literary status the three mentioned books are selected, studied and analyzed in this article.